Bone marrow and macrophage functions as determinants of bovine trypanotolerance - Anosa, V.O.; Logan-Henfrey, L.L.; Wells, C.W. (OAU/STRC, 1995)
Sequential changes in the blood and bone marrow (BM) were studied by light and transmission electron microscopy in three Boran and three Ndama cattle before and after a primary infection with Trypanosoma congolense IL 1180. Parasitaemia was essentially similar in the Borans and the Ndamas between day 11 post-infection (DPI) and 59 DPI. Thereafter, until 112 DPI when the study was terminated, parasitaemia was higher in the Boran than in the Ndama. During the acute phase, the infection induced anaemia and leucopaenia which were milder in the Ndama than in the Boran. In the chronic phase, the leucocyte numbers and PCV of the Ndama improved, approaching pre-infection levels, whereas the values for the Boran continued to drop. Moderate thrombocytopaenia developed in the two breeds of cattle with no remarkable differences between them. The cellularity of BM biopsies were similar in the two breeds before infection. Following infection, the BM biopsies of Ndama cattle were consistently hypercellular while those of the Boran were hypocellular. The infection caused marked erythroid hyperplasia with marked hypoplasia of granulocyte elements in the Boran while there were only moderate corresponding shifts in these cell lineages in the Ndama. There was moderate hyperplasia of macrophages (Mo) in the bone marrow of both breeds, and the calculated volume index of Mo was 19.5 (+ or -) 3.6 in the Boran and 33.2 (+ or -) 3.9 in the Ndama (D<0.005) compared to 5.3 (+ or -) 1.4 and 4.7 (+ or -) 0.6 respectively, before infection. The Mo of both breeds were activated as shown by their significantly increased sizes and organelle (mitochondria, ER) contents, but those of the Ndama were more activated. The Mo in the BM phagocytosed immature and mature haemopoietic cells in the BM pariticulary erythrocytes, granulocytes and thrombocytes and smaller numbers of lymphoid cells and monocytes. Cells phagocytosis was preceded by cell to Mo attraction, and then adhesion. Prior to infection, the Mo had contacts with haemopoietic cells through V- or U-shaped microvilli apparently associated with Mo control of haemopoiesis; these contacts increased during infection. Target cell adhesion to Mo and phagocytosis, and contacts with haemopoietic cells were more marked with Mo of the Ndama than in the Boran, and these activities were further reduced in the boran on 98 and 112 DPI. In conclusion, it would appear that the Ndama achieve this superior tolerance because of hypercellularity of the BM and the greater activation of the Mo which result in greater haemopoiesis. Since cytophagia was also greater in the Ndama, our results indicate that this breed produces more blood cells and destroys more than the Boran. The balance between production and destruction appears to be much greater in the Ndama than in the Boran. The results of this study show that the BM is the key determinant organ of trypanotolerance in cattle while the Mo, particularly those of the BM, form the pivot of this control.